Effect of Microwave and Ultrasound-Assisted Extraction on the Phytochemical and In Vitro Biological Properties of Willow (Salix alba) Bark Aqueous and Ethanolic Extracts - Ricardo S. Aleman; Jhunior Marcia; Carmen Duque-Soto; Jesús Lozano-Sánchez; Ismael Montero-Fernández; Juan A. Ruano; Roberta Targino Hoskin; Marvin Moncada (Plants, 2023)
White willow (Salix alba) is a medicinal plant used in folk medicine. In this study, aqueous and ethanolic willow bark extracts were obtained via ultrasonic-assisted extraction (UAE) and microwave-assisted extraction (MAE), and analyzed regarding their phytochemical (total phenolics, phenolic acids, flavonoids, and tannins) content and in vitro biological properties (antibacterial and antifungal activity, acetylcholinesterase AChE inhibitory activity and anti-inflammatory effects). The highest phenolic, tannin, and flavonoid contents were found for willow bark extracts obtained via microwave-assisted extraction using ethanol as a solvent (SA-ME). The polyphenol load of all MAE and UAE extracts was higher when conventional solid–liquid extraction was applied (ρ < 0.05). The antioxidant capacities were stronger for microwave-assisted ethanolic extracts, with the lowest IC50 values of 12 μg/mL for DPPH• and a value of 16 μg/mL for ABTS•+, whereas the conventional extraction had the highest IC50 values (22 μg/mL and 28 μg/mL, respectively). Willow bark extract showed antibacterial activity against Gram-positive bacteria S. aureus and P. aeruginosa. AChE inhibitory activity was dependent on the extraction method and solvent used, and the highest inhibition among samples was observed for SA-ME. Taken altogether, our findings suggest that willow (Salix alba) bark extract obtained via ethanolic microwave-assisted extraction is a phytochemical-rich resource with in vitro, anti-inflammatory, and AchE inhibitory properties and, therefore, potential multiple medicinal end-uses.